Queen of America : a novel - Urrea, Luis Alberto (Little, Brown, 2011)
The remarkable heroine of The hummingbird's daughter returns in this epic novel of love and loss in a restless America. Teresita's passage will take her across the nation as she comes to terms with her place in a new world. She must finally ask herself the ultimate question: is a saint allowed to fall in love?